Electrocatalysis of Hydrogen Peroxide Generation Using Oxygen-Fed Gas Diffusion Electrodes Made of Carbon Black Modified with Quinone Compounds - Rocha, Robson S.; Valim, Ricardo B.; Trevelin, Leandro C.; Steter, Juliana R.; Carneiro, Jussara F.; Forti, Juliane C. [UNESP]; Bertazzoli, Rodnei; Lanza, Marcos R. V. (Springer Nature, 2020)
Hydrogen peroxide (H2O2) is one of the most popular and widely used oxidants. Among the wide range of synthesis techniques used for the production of H2O2; the electrochemical method allows the use of gas diffusion electrodes to generate H2O2 without limiting the low solubility of O2 in water. The present work reports the modification of carbon black with quinone, where the generation of H2O2 occurs in an electrochemical/chemical mechanism. The results obtained by this technique were found to be highly promising. The use of the organic compound 1,2-dihydroxyanthraquinone to modify carbon black electrode resulted in greater production of H2O2. Carbon black electrode modified with 1% of 1,2-dihydroxyanthraquinone yielded 298 mg L−1 of H2O2 at the end of 90 min of experiment, reaching an electrical efficiency of approximately 25.5%. Based on the findings of this study, H2O2 generation is found to be directly associated with the chemical structure of the carbon modifier and not solely related to the presence of quinone groups. [Figure not available: see fulltext.].
Keywords: Catalysis of oxygen reduction reaction; Electrosynthesis of hydrogen peroxide; Gas diffusion electrode; Quinone compounds